Secured approach for authentication using threshold-based hierarchical visual cryptography. (2015) - Chavan, Pallavi Vijay; Atique, Mohammad
Threshold based hierarchical visual cryptography is a novel approach in the field of visual cryptography. THVC is encrypting the secret information in number of levels. THVC encrypts the secret in such a way that decoding is performed easily by human visual system. The authors used standard threshold of 0.5 to determine the existence of information in share. The authors have experimented THVC for multiple thresholds ranging from zero to one. Two different authentication models are proposed based on THVC: one way authentication model, and two way authentication model. Shares generated out of THVC are used for authentication. One-way hashing is applied on all the shares to reduce the time complexity. 100% randomness is observed in generated shares. The percentage of pixel expansion is found to be 0% during experimentation. The parameters like peak signal to noise ratio, pixel expansion ratio, and number of shares are evaluated and compared with existing figures.